Giant anomalous Hall and Nernst effect in magnetic cubic Heusler compounds - Noky, Jonathan; Zhang, Yang; Gooth, Johannes; Felser, Claudia; Sun, Yan (npj Computational Materials, 2020)
The interplay of magnetism and topology opens up the possibility for exotic linear response effects, such as the anomalous Hall effect and the anomalous Nernst effect, which can be strongly enhanced by designing a large Berry curvature in the electronic structure. Magnetic Heusler compounds are a promising class of materials for this purpose because they are versatile, show magnetism, and their electronic structure hosts strong topological features. Here, we provide a comprehensive study of the intrinsic anomalous transport for magnetic cubic full Heusler compounds and we illustrate that several Heusler compounds outperform the best so far reported materials. The results reveal the importance of symmetries, especially mirror planes, in combination with magnetism for giant anomalous Hall and Nernst effects, which should be valid in general for linear responses (spin Hall effect, spin orbital torque, etc.) dominated by intrinsic contributions.
CRIS-Team Scopus Importer:2022-04-14